Profit Shifting by Multinationals and the Ownership Share: Evidence from European Micro Data - Matthias Dischinger (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2008)
We provide indirect empirical evidence of profit shifting behavior by multinational enterprises (MNEs) employing a panel study for the years 1995 to 2005, while controlling for unobservable fixed firm effects. We use a large micro database of European MNEs which includes detailed accounting and ownership information. Our results show a strongly negative relationship between an affiliated company's statutory corporate tax rate difference to its foreign parent firm and the affiliate's gross profits. Quantitatively, a 10 percentage points decrease in the tax rate of the affiliate (relative to the parent) increases its pre-tax profitability by 7%, other things being equal. Various robustness checks support this profit shifting inference. Furthermore, we provide evidence that a higher parent's ownership share of its subsidiary leads to intensified shifting activities between these two affiliates.
urn:nbn:de:bvb:19-epub-5661-6
Keywords: H25; H26; F23; C33; 330; corporate taxation; multinational enterprise; profit shifting; share ownership ratio; micro level data; Gewinnverlagerung; Multinationales Unternehmen; Ausländische Tochtergesellschaft; Eigentümerstruktur; Nationalkultur; Schätzung; Europa